Results on mating disruption by sex pheromones against moth pests of apple in integrated and organic orchards - Újvári, I.; Holb, I. J. (International Journal of Horticultural Science, 2007)
The study was aimed to study that how mating disruption by hand applied dispensers can reduce the number of damage caused by Cydia pomonella, Adoxophyes orana and Pandemis heparana in four integrated and organic apple orchards. In the first orchard (Gacsály), protection against moth caterpillars ensured by IPM and conventional production systems were equally good, but worse than that of the orchard part where mating disruption was applied by 1000 dispensers/ha. In second orchard (Nyírbogdány), the highest incidence of codling moth damage was measured in the hilly part (17%), while in the plot where 440 dispensers/ha pheromone dosage was applied, the damage incidence was 11%. The smallest damage incidence was at the flat part, where 666 dispensers /ha was applied. In the third and fourth orchards (Eperjeske), codling moth damage on fruits was below 7% in the larger and smaller orchards where 1000 dispensers/ha was applied. At Eperjeske, the codling moth damage increased by 32.3% in the field treated with Bacillus thuringiensis product but without using mating disruption. The results verified that the use of 1000 dispensers/ha as suggested by the manufactures is essential, especially in the first year of application. The results also suggested that better results can be achieved in flat areas and the larger plot size also enables a more efficient reduction of the damage.